Genetic Interaction between Arabidopsis Qpm3.1 Locus and Bacterial Effector Gene hopW1-1 Underlies Natural Variation in Quantitative Disease Resistance to Pseudomonas Infection - Luo, Qi; Liu, Wei-Wei; Pan, Ke-Di; Peng, You-Liang; Fan, Jun (Frontiers in Plant Science, 2017)
Wide quantitative variation in plant disease resistance across Arabidopsis wild populations has been documented and the underlying mechanisms remain largely unknown. To investigate the genetic and molecular basis of this variation, Arabidopsis recombinant inbred lines (RILs) derived from Aa-0Col-0 and Gie-0Col-0 crosses were constructed and used for inoculation with Pseudomonas syringae pathovars maculicola ES4326 (ES4326) and tomato DC3000 (DC3000). Bacterial growth assays revealed continuous distribution across the large differences between the most and the least susceptible lines in the RILs. Quantitative trait locus (QTL) mapping analyses identified a number of QTLs underpinning the variance in disease resistance, among which Qpm3.1, a major QTL on chromosome III from both Aa-0 and Gie-0 accessions, preferentially restricted the growth of ES4326. A genetic screen for the ES4326 gene selectively leading to bacterial growth inhibition on accession Aa-0 uncovered the effector gene hopW1-1. Further QTL analysis of disease in RILs inoculated with DC3000 carrying hopW1-1 showed that the genetic interaction between Qpm3.1 and hopW1-1 determined Arabidopsis resistance to bacterial infection. These findings illustrate the complexity of Arabidopsis-Pseudomonas interaction and highlight the importance of pathogen effectors in delineating genetic architectures of quantitative variation in plant disease resistance.